Pengaruh Model Pembelajaran Savi Terhadap Hasil Belajar Siswa Pada Tema 1 Subtema 1 Organ Gerak Hewan Kelas V SD Negeri 097320 Serapuh - Naomi Srirejeki Harianja; Yanti Arasi Sidabutar; Sudirman T P Lumbangaol (CV. KAMPUS AKADEMIK PUBLISING, 2023)
The purpose and influence of the SAVI Learning Model. This research was conducted at SD Negeri 097320 Serapuh. Quantitative research using experimental techniques is the methodology used. This research uses a Pre-Experimental